Peran Komunikasi Pembangunan dalam Pemberdayaan Masyarakat Pesisir - S. Amanah (Jurnal Komunikasi Pembangunan, 2010)
Status and condition of coastal community relate to several factors included ecological characteristics, socioecconomic and cultural characteristics, natural and geographical characteristics, government policy, local wisdomand knowledge, and their cosmopolites. Up to now, the coastal community especially small fishery communities stillface the problems of lack of information, limited access of asset and capital, and dependency to the externalassistances. This situation was also found at the north Bali, whereas most of the fishery communities ran theirbusinesses traditionally. Effective development communication strategy and program would help the community to bemore aware of coastal resources management. The study was conducted at the Gerokgak and Buleleng District,North Bali. A number of 128 respondents involved in the research and 10 informal leaders contributed informationabout various program in the region. Research results showed that development communication was urged to beable to provide more facilitation in terms of empowering the fishery group, capacity improvement of the group incoastal resources management; enlarging people choices, implementing participatory approaches, and strengtheningnetwork to support the community in managing the business.